Light emitting diode with suppressed electronic leakage current

By mixing luminescent nanoparticles and insulating materials in the emission layer of the quantum rod light-emitting diode, the problems of electron leakage current and Foster resonance energy transfer are solved, and the efficiency and stability of the device are significantly improved.

CN119816093APending Publication Date: 2025-04-11THE HONG KONG UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411391256.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-10-10
Filing Date
2024-10-08
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

Existing quantum dot light emitting diodes (QLEDs) have reduced efficiency under high brightness drive, and problems such as electron leakage current and Foster resonance energy transfer (FRET) affect their performance and stability.

Method used

By mixing luminescent nanoparticles and insulating materials in the emission layer, the insulating material fills the voids in the emission layer, blocking electron leakage current and reducing FRET, thereby improving photoluminescent quantum yield and external quantum efficiency.

Benefits of technology

The external quantum efficiency, current efficiency and brightness of the quantum rod light emitting diode (QRLED) is significantly improved, the driving voltage is reduced, and the charge balance and stability of the device is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119816093A_ABST
    Figure CN119816093A_ABST
Patent Text Reader

Abstract

A light emitting device (LED) includes a substrate, an anode layer disposed on the substrate, a hole injection layer disposed on the anode layer, a hole transport layer disposed on the hole injection layer, an emission layer disposed on the hole transport layer, an electron transport layer disposed on the emission layer, and a cathode layer disposed on the electron transport layer. At least one of the anode layer and the cathode layer is transparent. The emissive layer includes a mixture of luminescent nanoparticles and an insulating material.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims priority to U.S. Provisional Patent Application Serial No. 63 / 589,032, filed on October 10, 2023, entitled “Light Emitting Diodes With Supressed Electron Leakage Current,” which is hereby incorporated by reference in its entirety. Technical Field

[0003] The present disclosure relates generally to light emitting diodes (LEDs). Background Art

[0004] The reference to any prior art in this specification does not constitute an acknowledgement or implication that the prior art forms part of the common general knowledge in any jurisdiction, nor does it imply that the prior art could reasonably be expected to be understood, regarded as relevant and / or combined with other prior art by a person skilled in the art.

[0005] Colloidal semiconductor quantum dots (QDs) have recently shown great interest in realizing efficient and low-cost LEDs for future display and lighting applications, compared to organic or metal-organic light emitters. QDs are able to tune the emission color in the visible spectrum by varying the core size, narrow emission linewidth, high quantum yield, good stability, and solution processability. These advantages make them attractive star materials for the fabrication of quantum dot light-emitting diodes (QLEDs). Recent developments in liquid crystal display (LCD) technology have prompted the adoption of QD color-enhancing films to improve brightness and display output. However, current research has mainly focused on electrically driven quantum dot LEDs due to their self-emissive properties, excellent color gamut, and brightness compared to down-converters.

[0006] Over the past two decades, a large number of researchers have devoted their efforts to synthesizing QDs, optimizing device structures, and improving electron-hole transport in QLEDs. The result is a high light quantum yield (PLQY) of over 90%, a smooth carrier injection barrier, and an ideal charge balance. These advances have enabled QLEDs to achieve commercial efficiency and stability standards in the display and lighting industries. Recently demonstrated red, green, and blue QLEDs achieved an external quantum efficiency (EQE) of over 20%, the theoretical limit for conventional QLED structures, and achieved an initial brightness of 100 cd / m^2 (m^2 vs. m 2 The device operating life T50 of red and green QLEDs exceeds 100,000 hours when the area is the same, i.e. square meters).

[0007] Despite the progress made in QLEDs, challenges remain, such as the change in PLQY from solution to solid film, EQE fluctuations, and the interpretation of efficiency between different batches or different devices. Peak EQE is usually reported at lower brightness levels (1 to several hundred cd / m^2). However, when the device is driven at high current to achieve higher brightness, the EQE can drop significantly due to various reasons including Joule heating, charge imbalance, Auger recombination (AR) loss, and organic HTL degradation. Recent research on QLEDs has focused on addressing the above factors by optimizing the device structure to improve charge injection and minimize leakage current to suppress Joule heating. This includes adding an electron blocking layer (EBL) to the device to prevent excessive electron injection into the QD while allowing efficient hole injection to maximize charge balance. In addition, covering the QD with a thicker shell can increase the emissive core interdot distance in the tightly packed QD film, thereby minimizing Forster resonance energy transfer (FRET) in the film. These methods aim to improve the efficiency and stability of QLEDs to meet the needs of practical device applications. Summary of the invention

[0008] According to one or more embodiments, a light emitting device (LED) is provided. The LED includes a substrate, an anode layer arranged on the substrate, a hole injection layer arranged on the anode layer, a hole transport layer arranged on the hole injection layer, an emission layer arranged on the hole transport layer, an electron transport layer arranged on the emission layer, and a cathode layer arranged on the electron transport layer. At least one of the anode layer and the cathode layer is transparent. The emission layer includes a mixture of luminescent nanoparticles and an insulating material.

[0009] In one or more embodiments, an insulating material fills the voids formed in the emission layer.

[0010] In one or more embodiments, the insulating material is an organic material. For example, the organic material includes one or more types of aliphatic hydrocarbons or mixtures thereof.

[0011] In one or more embodiments, the organic material comprises a polymer. For example, the polymer is selected from the group consisting of rubber, PTFE, PET, PMMA, PS, PE, PP and PET.

[0012] In one or more embodiments, the organic material is paraffin wax.

[0013] In one or more embodiments, the insulating material and the luminescent nanoparticles used to deposit the emissive layer can be dissolved in the same solvent.

[0014] In one or more embodiments, the luminescent nanoparticles are spherical nanoparticles.

[0015] In one or more embodiments, the luminescent nanoparticles are anisotropic nanoparticles. For example, the anisotropic nanoparticles are nanosheets.

[0016] In one or more embodiments, one or more of the luminescent nanoparticles has a structure selected from the group consisting of: a core-shell structure, a core-gradient shell structure, a core-double shell structure, a core-gradient shell-shell structure, and a gradient core-shell structure.

[0017] In one or more embodiments, the luminescent nanoparticles include semiconductor nanoparticles. For example, the semiconductor nanoparticles are selected from the group consisting of: CdSe nanoparticles, CdS nanoparticles, ZnSe nanoparticles, ZnSe nanoparticles, InP nanoparticles, CuInS2 nanoparticles, AgInS2 nanoparticles, CdTe nanoparticles, ZnTe nanoparticles, and ZnO nanoparticles.

[0018] In one or more embodiments, the luminescent nanoparticles are perovskite nanoparticles.

[0019] In one or more embodiments, the insulating material is attached to the surface of the luminescent nanoparticles by covalent or non-covalent chemical bonding (or chemical bond), thereby acting as a ligand. For example, the ligand can provide anisotropic current conduction. In one or more embodiments, the ligand has an anisotropic shape. For example, the anisotropic shape is T-shaped or Π-shaped.

[0020] In one or more embodiments, the ligand includes a conjugated aromatic system.

[0021] In one or more embodiments, the mixture of insulating materials in the emission layer can prevent short channels between hole and electron transport layers.

[0022] In one or more embodiments, the insulating material may prevent foreign materials from penetrating into the emission layer, and the insulating material is coated in a subsequent layer after the emission layer material.

[0023] In one or more embodiments, the insulating material in the emissive layer acts as an electron blocking layer.

[0024] In one or more embodiments, the insulating material reduces Forster resonance energy transfer (FRET) between thin films of luminescent nanoparticles, thereby increasing the photoluminescence quantum yield of these nanoparticles encapsulated in the film.

[0025] In one or more embodiments, the LEDs exhibit higher external quantum efficiency and current efficiency compared to reference devices without admixed insulating materials.

[0026] In one or more embodiments, the LED exhibits higher brightness compared to a reference device without the admixture of the insulating material.

[0027] In one or more embodiments, the LEDs exhibit lower drive voltages required to achieve maximum brightness, external quantum efficiency, and current efficiency compared to reference devices without insulating materials.

[0028] In one or more embodiments, the LED exhibits a better charge balance of positive and negative charge carriers injected into the emitting material compared to a reference device without admixing the insulating material.

[0029] Other example embodiments are also discussed herein. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] The detailed description is set forth with reference to the accompanying drawings. The drawings are for illustration only and describe only example embodiments of the present disclosure. The drawings are provided to facilitate understanding of the present disclosure and should not be considered to limit the breadth, scope, or applicability of the present disclosure. Unless otherwise noted, the drawings are not drawn to scale. For ease of explanation, certain parts of the drawings are exaggerated and should not be considered limiting unless otherwise noted.

[0031] Figure 1 An LED according to certain embodiments of the present disclosure is shown.

[0032] Figure 2 Quantum rods (QRs) according to certain embodiments of the present disclosure are shown: (a) transmission electron microscopy (TEM) images of QRs with different lengths; and (b) schematic illustrations of corresponding QR films.

[0033] Figure 3 Schematic illustration of the manufacture of quantum rod (QR)-based light-emitting devices (QRLEDs) according to certain embodiments of the present disclosure: (a) QR film without paraffin doping; (b) QR / ZnMgO without paraffin doping; (c) device structure without paraffin doping; (d) QR film doped with paraffin; (e) QR / ZnMgO doped with paraffin; and (f) device structure doped with paraffin.

[0034] Figure 4 Energy dispersive X-ray spectroscopy (EDX) of cross-sectional TEM images of QR LEDs according to certain embodiments of the present disclosure are shown: (a) and (c) with insulating material doped in the QR; and (b) and (d) without insulating material doped in the QR.

[0035] Figure 5Curves of (a) JV (current density versus voltage), (b) LV (luminance versus voltage), (c) EQE-J (external quantum efficiency versus current density), and (d) CE-J (current efficiency versus current density) of QRLEDs according to certain embodiments of the present disclosure are shown, respectively, as a function of ZnMgO thickness optimization and QR length variation. DETAILED DESCRIPTION

[0036] The present disclosure will now be described with reference to the following examples, which are to be considered in all respects as illustrative rather than restrictive.

[0037] Throughout the specification and claims, the words "include", "including", etc. should be understood to be inclusive rather than exclusive or exhaustive; that is, they should be understood to mean "including but not limited to".

[0038] In addition, as used herein, unless otherwise specified, the use of ordinal adjectives "first", "second", etc. to describe common objects merely indicates that different instances of the same type of objects are referred to, and does not mean that the objects so described must be in a given sequence in time, space, order, or any other aspect.

[0039] Example embodiments relate to light emitting diodes having improved performance, such as light emitting diodes having suppressed or reduced electron leakage current.

[0040] The inventors studied the development of QDs in display technology, explored other types of nanomaterials, such as semiconductor nanorods (NR) or QRs, and realized that they have additional optical advantages over QDs. In some examples, a spherical nano-sized cadmium selenide (CdSe) core is surrounded by an elongated CdSe shell called a QR or NR. Therefore, QR has similar optical properties to QDs, but with the advantage of increased shape anisotropy. Compared with spherical QD films, the elongated shape of QRs gives the emission cores in the aligned QR films a larger spatial spacing, thereby reducing energy transfer (ET) in the QR films. In addition, the band structure of QRs can also delocalize electrons along the longitudinal axis of the rod, while holes remain tightly bound to the core, which effectively suppresses Auger recombination (AR) losses. In addition, depending on the shape and structure of the QR, the QR exhibits a large Stokes shift and linearly polarized emission along its longitudinal axis. The horizontally oriented dipoles of the QR enable polarized emission. Therefore, when the QR is embedded in the LED structure, the QR achieves a higher outcoupling efficiency (η out ), which is twice higher than that of spherical QDs (20%). The high linear polarization emission of QR films has the potential to replace the front polarizer film in LCD displays, enabling thinner, more flexible and more efficient colorful and vivid displays.

[0041] Despite their potential advantages over conventional QDs in display and lighting applications, QRs remain to be explored compared to QDs. Several factors have hampered the exploration of QRs in lighting and display applications. One of the main factors is the lack of synthesis technology capable of covering the entire visible spectrum using QRs, and the relatively low device electroluminescence (EL) efficiency of QRs compared to QDs. The present inventors have synthesized QRs covering the entire visible spectrum and verified their LED (QRLED) performance.

[0042] However, the efficiency of QRLEDs lags behind that of QLEDs, which is caused by several factors. The first problem is that the PLQY of QRs decreases significantly from solution to solid-state films, which is due to Forster resonance energy transfer (FRET) between tightly packed QRs. FRET in spin-cast QR films is significantly higher than that in spherical QD films. When QRs are spin-coated, they are randomly distributed on the substrate and most QRs overlap with neighboring rods, resulting in the distance between emitting cores in QR films being closer than the interdot FRET radius, which is typically less than 9nm. This leads to efficient FRET and a significant red shift in the photoluminescence (PL) spectrum, thereby quenching the PL intensity.

[0043] The PLQY is reduced due to FRET from one QR to the adjacent QR through multiple FRET pathways, which results in heat dissipation instead of light emission. In addition to FRET and PLQY, electron leakage current is another important parameter that affects the performance and stability of QRLEDs. Due to the overlap of QRs, the spin-coated QR film produces small voids and gaps, which are filled by the next layer of zinc magnesium oxide (ZnMgO) nanoparticles (NPs) during the device fabrication process. As a result, the ZnMgO NPs partially mix with the QRs and directly enter the hole transport layer. This leads to overcharging of electrons in the QRs, resulting in high leakage current, efficient FRET, and electron-hole recombination zones away from the QRs, resulting in higher non-emission current, reduced PLQY of the QRs, and charge imbalance in the device. These factors lead to low device efficiency, high energy efficiency degradation, and device instability due to thermally induced Joule heating in the device. In addition, it has been found that the leakage current in QRLEDs increases with respect to the aspect ratio of the QR.

[0044] QR alignment techniques improve the QR film morphology, prevent QR overlap in the film, and ensure that the inter-point distance is greater than the FRET radius, which can maintain the emission characteristics of the QR in the film and block direct contact between the ETL and HTL in the device. QR alignment techniques include self-alignment, mechanical friction, Langmuir-Blodgett technique, stretch-induced assembly, etc. However, these methods have limitations in scalability, compatibility with standard device manufacturing processes, and the ability to produce QR alignment quality covering a large area. Therefore, how to obtain efficient QRLEDs by avoiding FRET and leakage current in devices with the help of traditional manufacturing methods remains a huge challenge.

[0045] For LEDs that include light-emitting nanoparticles (such as semiconductor nanoparticles), their efficiency depends on factors including: (1) the fraction of photons generated per injected carrier, i.e., the internal quantum efficiency (IQE); and (2) the efficiency with which these photons are coupled out of the device (η out ). The IQE in turn depends on the PLQY and the fraction of positive and negative charge carriers injected into the emission center. The disadvantages of conventional LED structures with semiconductor nanoparticles include: (1) low hole injection efficiency compared to electron injection due to the lower mobility of organic hole transport materials (HTMs) than the commonly used inorganic electron transport materials (ETMs), and a larger energy barrier for hole injection into the emission layer due to the shallow highest occupied molecular orbital (HOMO) of the commonly used organic hole transport layer (HTL) and the deep HOMO energy level of the semiconductor nanoparticle emission layer (EML); (2) the presence of interface defects between multiple stacked layers, resulting in leakage currents and non-radiative recombination centers at the interfaces between stacks; (3) complex control of the separation between individual nanoparticles in the emission layer using organic ligands; (4) the need to add an electron blocking layer between the electron transport layer (ETL) and the emission layer to suppress excess electron current and balance charge injection; (5) in addition to the above, FRET in the emission layer, interfaces (intermixing) between HTL / EML / ETL, and electron leakage current (ETL is in direct contact with the HTL through the voids / gaps in the EML) are serious problems in semiconductor QRLEDs.

[0046] Example embodiments address one or more of these problems associated with the prior art and achieve performance improvements, such as mitigating or avoiding FRET and reducing electron leakage current.

[0047] One or more embodiments address the issues of FRET and / or leakage current in QRLEDs by proposing a simple and cost-effective approach.

[0048] One or more embodiments provide an LED having an emitting layer, wherein the emitting layer includes a mixture of luminescent nanoparticles and an insulating material.

[0049] One or more embodiments provide a QR film for addressing voids / gaps in existing QR films.

[0050] One or more embodiments mix paraffin wax with QR before coating the QR layer to fill voids and gaps in the QR film during QRLED manufacturing. The paraffin wax layer acts as a spacer between adjacent QRs, thereby blocking electron leakage current and suppressing FRET. This method does not require any additional processing steps or tools and increases the PLQY of the QR film from 33% to 64%. By optimizing the ratio of paraffin wax to QR, the electroluminescent properties of QRLEDs were confirmed: EQE was improved by two times and the brightness was improved by 1.5 times. These findings provide valuable insights into the manufacture of QRLEDs and provide new opportunities for practical device applications.

[0051] Figure 1 An LED 100 is shown according to certain embodiments of the present disclosure.

[0052] The LED 100 includes a substrate 110, a bottom electrode or anode layer 120 disposed on the substrate 110, a hole injection layer (HIL) 130 disposed on the anode layer 120, a hole transport layer (HTL) 140 disposed on the HIL 130, an emission layer (EML) 150 disposed on the HTL 140, an electron transport layer (ETL) 160 disposed on the EML 150, an electron injection layer (EIL) 170 disposed on the ETL 160, and a top electrode or cathode layer 180 disposed on the EIL 170. At least one of the anode layer 120 and the cathode layer 180 is transparent. The EML 150 includes a mixture of luminescent nanoparticles and an insulating material.

[0053] It will be understood that EIL 170 is optional. In some embodiments, cathode layer 180 is disposed directly on ETL 160 without including any separate EIL.

[0054] The substrate 110 may be a rigid substrate or a flexible substrate. For example, the substrate 110 may be a glass substrate, a silicon substrate, a silicon nitride substrate, etc., or a combination thereof. The substrate 110 may be a single substrate or a stack of two or more substrates.

[0055] The anode layer 120 is a conductive electrode. In one or more embodiments, the anode layer 120 includes a transparent conductive metal oxide such as indium tin oxide (ITO), fluorine-doped tin oxide (FTO), zinc oxide (ZnO), indium tin zinc oxide (ITZO), and the like.

[0056] In one or more embodiments, the HIL 130 includes one or more compounds that are conductive, such as poly(3,4-ethylenedioxythiophene)(styrenesulfonate) (PEDOT:PSS), 1,4,5,8,9,11-hexaazatriphenyl-hexanitrile (HATCN), molybdenum trioxide (MoO3), nickel oxide (NiO), tungsten trioxide (WO3), etc.

[0057] In one or more embodiments, the HTL 140 includes one or more small or large polymers, such as polyvinylcarbazole (PVK), poly[9,9-dioctylfluorene-2,7-diyl]-co-N,N'-bis(4-butylphenyl)-N,N'-bis(phenyl)benzidine (TFB), 4,4'-bis(N-carbazolyl)-1,1'-biphenyl (CBP), 1,3-bis(N-carbazolyl)benzene (mCP), etc.

[0058] In one or more embodiments, the ETL 160 includes one or more of ZnO, ZnMgO, titanium dioxide (TiO 2 ), aluminum-doped zinc oxide (AlZnO), and the like.

[0059] In one or more embodiments, the EIL 170 includes one or more of lithium fluoride (LiF), lithium peroxide (LiO 2 ), and the like.

[0060] In one or more embodiments, the cathode layer 180 includes one or more of Al, Ag, Au, Pt, Pd, and the like.

[0061] The luminescent nanoparticles may be anisotropic nanoparticles or isotropic nanoparticles. The luminescent nanoparticles may include nanoparticles of various shapes, including but not limited to QDs, QRs, nanoplates (NPLs), and perovskite nanoparticles. In some embodiments, the luminescent nanoparticles are spherical nanoparticles.

[0062] In some embodiments, QR is used to illustrate the concept of the present invention. The aspect ratio of QR may be equal to or greater than 1:4 (such as 5 nm in width and 20 nm in length).

[0063] In some embodiments, all luminescent nanoparticles in EML 150 are of the same type, such as all QRs. In some embodiments, the luminescent nanoparticles in EML 150 may be a combination of two or more types of nanoparticles, such as a combination of QDs and QRs.

[0064] In some embodiments, the structure of one or more luminescent nanoparticles is selected from the group consisting of core-shell structure, core-gradient shell structure, core-double shell structure, core-gradient shell-shell structure and gradient core-shell structure. Nanoparticles with other types of structures are also possible.

[0065] In some embodiments, the luminescent nanoparticles include semiconductor nanoparticles, including but not limited to CdSe nanoparticles, CdS nanoparticles, ZnS nanoparticles, ZnSe nanoparticles, InP nanoparticles, CuInS2 nanoparticles, AgInS2 nanoparticles, CdTe nanoparticles, ZnTe nanoparticles, and ZnO nanoparticles.

[0066] In some embodiments, the luminescent nanoparticles include QRs selected from the group consisting of CdSe nanoparticles, CdS nanoparticles, core-shell NPs, perovskite NPs, and NPLs.

[0067] In some embodiments, the insulating material may be selected from the group consisting of hydrocarbons (particularly saturated hydrocarbons) or mixtures of different hydrocarbons such as paraffins, density, melting point polymers / monomer compounds, inorganic materials, and the like.

[0068] In some embodiments, the insulating material is or includes an organic material.The term "organic material" as used herein should be broadly understood as "one or more organic materials", unless explicitly stated to the contrary.

[0069] In some embodiments, the organic material comprises a polymer. The polymer may be selected from the group consisting of rubber, polytetrafluoroethylene (PTFE), polyethylene terephthalate (PET), polymethyl methacrylate (PMMA), polystyrene (PS), polyethylene (PE), and polypropylene (PP).

[0070] In some embodiments, the organic material is paraffin.As used herein, the terms "paraffin wax" and "paraffin" are used interchangeably.

[0071] In some embodiments, the insulating material is attached to the surface of the luminescent nanoparticles by covalent or non-covalent chemical bonding (or chemical bond, chemicalbound), thereby acting as a ligand. The ligand provides anisotropic current conduction in the EML. Therefore, the ligand can change the optical and electronic properties of the nanoparticles and improve the overall efficiency and durability of the LED. In some embodiments, the ligand has an anisotropic shape, such as a T-shape or a II-shape. In some embodiments, the ligand includes a conjugated aromatic system. That is to say, the insulating material has an aromatic structure that contributes to the electronic properties of the nanoparticles.

[0072] The weight ratio of the luminescent nanoparticles to the insulating material in the EML can vary. In some embodiments, the weight ratio can be in the range of 1:0.5 to 1:2.5, such as 1:0.5, 1:1, 1:1.5, 1:2, 1:2.5. The weight ratio can be adjusted to optimize device performance. The optimized weight ratio may depend on factors such as the properties of the nanoparticles, such as the material, size, shape, etc. of the nanoparticles.

[0073] In some embodiments, the insulating material is dissolved in the same solvent as the luminescent nanoparticles used to deposit the emissive layer. That is, the insulating material and the luminescent nanoparticles can be dissolved in the same solvent.

[0074] When a mixture of luminescent nanoparticles and insulating materials is used, the insulating material can fill the voids or gaps in the emission layer. This can alleviate or reduce the short channels that are not expected to appear between the holes and the electron transport layer. In addition, the insulating material can also prevent foreign materials from penetrating into the EML. These foreign materials are often introduced when subsequent layers are coated after the emission layer material. Short channels and foreign materials are undesirable because they quench electrons and / or holes and / or electron-hole pairs, thereby reducing the efficiency of the LED. In this sense, the insulating material in the ELM acts as an electron blocking layer, which improves device performance. Additionally, the insulating material can also reduce FRET in the luminescent nanoparticle film, thereby improving the photoluminescence quantum yield of these nanoparticles encapsulated in the film.

[0075] In the example experiments, LEDs according to one or more embodiments ("embodiment LEDs") and reference devices were prepared and their performance was compared. The reference device (also referred to as the control device) is an LED that does not bond any insulating material in the EML. It has been demonstrated that the embodiment LEDs exhibit a better charge balance of positive and negative charge carriers injected into the emission material and have higher external quantum efficiency, current efficiency, and brightness than the reference device. In addition, the embodiment LEDs require a lower driving voltage to achieve maximum brightness, external quantum efficiency, and current efficiency.

[0076] Figure 2 QRs according to certain embodiments of the present disclosure are shown: (a) TEM images of QRs with different lengths (length and diameter range close to 4 nm); and (b) schematic illustrations of corresponding QR films. It can be seen that small voids or gaps exist in the QR film. These voids can cause leakage currents, which become more prominent when the QR length is short and are detrimental to the device performance of the LED. Increasing the length of the QR can reduce or decrease the void density and increase the interaction between adjacent QRs, thereby reducing the FRET effect. Therefore, optimizing the length of the QR can improve the performance of the QRLED.

[0077] Figure 3 Schematic illustrations of QRLED fabrication according to certain embodiments of the present disclosure: (a) QR film undoped with paraffin wax, (b) QR / ZnMgO undoped with paraffin wax, (c) device structure undoped with paraffin wax, (d) QR film doped with paraffin wax, (e) QR / ZnMgO doped with paraffin wax, and (f) device structure doped with paraffin wax.

[0078] In sub-figure (b), ZnMgO NPs are shown filtering the voids in the QR film and partially mixing with the QRs. In contrast, in sub-figure (e), the voids in the QR film are filled with paraffin wax, while the ZnMgO NPs simply rest on top of the QRs and paraffin wax. The complete QRLED structure in sub-figure (c) shows that the ZnMgO NPs filter the voids in the QR film and are in direct contact with the PVK, resulting in higher leakage current, higher FRET, and charge imbalance in the device. In contrast, in sub-figure (f), the interface between PVK / QR: paraffin wax / ZnMgO NPs is very clear, with no diffusion or mixing in and out of the stack, thereby improving device performance.

[0079] Figure 4 Cross-sectional TEM images EDX of QR LEDs according to certain embodiments of the present disclosure are shown: (a) and (c) with insulating material doped in the QR; and (b) and (d) without insulating material doped in the QR.

[0080] Figure 5 The (a) JV (b) LV (c) EQE-J and (d) CE-J curves of QRLEDs according to certain embodiments of the present disclosure are shown as a function of ZnMgO thickness optimization and QR length variation, respectively. As described below, the manufacturing process of devices 1 to 5 is essentially the same. The difference between the five devices is the weight ratio of the luminescent nanoparticles to the insulating material.

[0081] The device structure includes a glass substrate as a base, an anode (ITO), a HIL (PEDOT:PSS), a HTL (PVK), an EML (doped with an insulating material), an ETL (ZnMgO), an EIL, and a cathode (Al) in sequence. For each device, the cleaned ITO patterned glass substrate was treated with ozone plasma for 10 minutes before coating the PEDOT:PSS layer, followed by spin coating. The PEDOT:PSS Al 4083 solution filtered through a 0.45 μm nylon filter was spin coated onto the ITO at 3000 rpm for 40 seconds and then baked at 150°C for 20 minutes. The remaining PVK, EML, ZnMgO, and Al layers were fabricated in a storage box filled with N2. HTL PVK was dissolved in 8 mg / ml chlorobenzene (filtered through a 0.2 μm PTEF filter) and coated on top of the substrate at 3000 rpm for 40 seconds, followed by baking at 140°C for 20 minutes. The light-emitting layer QR was then spin-coated at 8 mg / ml in octane on the PVK-coated substrate at 3000 rpm for 45 seconds and baked at 80°C for 10 minutes. ZnMgO was then spin-coated at 3000 rpm in ethanol for 40 seconds on top of the substrate and treated at 80°C for 10 minutes. Finally, 100 nm of aluminum was deposited as the cathode by thermal evaporation with the aid of a micromask. The device is defined as the overlapping area of ​​ITO and Al, with an active area of ​​4.5 mm 2 .

[0082] The weight ratios of luminescent nanoparticles to insulating materials of devices 1 to 5 are 1:0, 1:0.5, 1:1.1, 1:1.5, and 1:2, respectively. It can be seen that the performance of device 3 or 4 is better than the other devices. This shows that the bonding of insulating materials helps improve device performance, such as reducing leakage current, improving brightness, and efficiency.

[0083] One or more embodiments provide a method for manufacturing an LED using luminescent nanoparticles in the form of QR as an example. The first step includes depositing a mixed solution containing QR doped with an insulating material onto a substrate using spin coating to prepare a QR film. The substrate is then annealed at a temperature below the glass transition temperature of the insulating material.

[0084] In the second step, a QRLED is provided. The QRLED includes a substrate, a pair of conductive electrode layers (at least one of which is transparent), a hole injection layer, a hole transport layer, a QR light emitting layer, an electron transport layer and an electron injection layer. The QR light emitting layer includes a mixture of light emitting nanoparticles and an insulating material.

[0085] The method for preparing a QR film according to one or more embodiments has various advantages. During the spin coating process, the QRs are mixed with the insulating material that settles to the bottom of the substrate, and they fill the voids or gaps in the QR film at the bottom. The remaining insulating material covers the top of the QR film. Therefore, the distance between points in the QR film is increased, which significantly improves the PLQY of the QR film.

[0086] The method for preparing a QRLED according to one or more embodiments has various advantages. The method helps to suppress leakage current between the HTL / QR / ETL interface, minimizes excess electron current entering the QR without an electron blocking layer, and improves charge balance in the device. These improvements significantly improve the electroluminescent properties of the QRLED.

[0087] As desired, the same or similar methods can be used for LEDs with other device structures with a bottom transparent anode and a top metal cathode, or can be used for an inverse device configuration with a bottom transparent cathode and a top metal anode. The same or similar methods can be used for a series configuration light emitting device with multiple EMLs.

[0088] One or more of the embodiments described herein all refer to QDs. However, it will be understood that this is for illustrative purposes only and that these embodiments are equally applicable, or mutatis mutandis, to luminescent nanoparticles other than QDs.

[0089] One or more embodiments describe one or more methods with specific conditions in terms of temperature, time, sequence, etc. It will be understood that this is for illustrative purposes only. The specific conditions for manufacturing one or more devices described herein may vary according to actual application conditions, such as adjustment, modification, replacement, omission, etc.

[0090] Nevertheless, the inventors have conducted various experiments and proved that QR can significantly improve the outcoupling efficiency of LEDs compared to spherical QDs. According to some experiments, the outcoupling efficiency of QRLED devices is twice that of quantum dot LEDs (QDLEDs) when both are mixed with the same insulating material.

[0091] It will be further understood that any features in the above embodiments of the present disclosure can be combined together and do not have to be applied in isolation from each other. Those skilled in the art can easily perform similar combinations of two or more features in the above embodiments or preferred forms of the present disclosure.

[0092] Unless otherwise defined, technical and scientific terms used herein have the ordinary meanings commonly understood by those skilled in the art to which the example embodiments belong. It will be appreciated by those skilled in the art that many variations and / or modifications may be made to the above-described embodiments without departing from the broad overall scope of the present disclosure. Therefore, the present embodiments should be considered in all respects as illustrative and not restrictive.

Claims

1. A light emitting device (LED), the LED comprising: substrate; an anode layer disposed on the substrate; a hole injection layer disposed on the anode layer; a hole transport layer disposed on the hole injection layer; an emission layer disposed on the hole transport layer; an electron transport layer disposed on the emission layer; as well as a cathode layer disposed on the electron transport layer, wherein at least one of the anode layer and the cathode layer is transparent, Wherein, the emission layer includes a mixture of luminescent nanoparticles and insulating materials.

2. The LED according to claim 1, wherein The insulating material fills the gaps formed in the emission layer.

3. The LED according to claim 2, wherein: The insulating material is an organic material.

4. The LED according to claim 3, wherein: The organic material includes one or more types of aliphatic hydrocarbons or a mixture thereof.

5. The LED according to claim 3, wherein: The organic material includes a polymer.

6. The LED according to claim 5, wherein: The polymer is selected from the group consisting of rubber, PTFE, PET, PMMA, PS, PE and PP.

7. The LED according to claim 3, wherein: The organic material is paraffin wax.

8. The LED according to claim 1, wherein: The insulating material can be dissolved in the same solvent as the luminescent nanoparticles used to deposit the emitting layer.

9. The LED according to claim 1, wherein: The luminescent nanoparticles are spherical nanoparticles.

10. The LED according to claim 1, wherein The luminescent nanoparticles are anisotropic nanoparticles.

11. The LED according to claim 10, wherein: The anisotropic nanoparticles are nanosheets.

12. The LED according to claim 1, wherein One or more of the luminescent nanoparticles has a structure selected from the group consisting of a core-shell structure, a core-gradient shell structure, a core-double shell structure, a core-gradient shell-shell structure, and a gradient core-shell structure.

13. The LED according to claim 12, wherein: The luminescent nanoparticles include semiconductor nanoparticles.

14. The LED according to claim 13, wherein: The semiconductor nanoparticles are selected from the group consisting of CdSe nanoparticles, CdS nanoparticles, ZnSe nanoparticles, ZnSe nanoparticles, InP nanoparticles, CuInS2 nanoparticles, AgInS2 nanoparticles, CdTe nanoparticles, ZnTe nanoparticles and ZnO nanoparticles.

15. The LED according to claim 1, wherein The luminescent nanoparticles are perovskite nanoparticles.

16. The LED according to claim 1, wherein The insulating material is attached to the surface of the luminescent nanoparticles through covalent or non-covalent chemical bonding, thereby acting as a ligand.

17. The LED according to claim 16, wherein The ligand provides anisotropic current conduction.

18. The LED according to claim 17, wherein The ligand has an anisotropic shape.

19. The LED according to claim 18, wherein The anisotropic shape is T-shaped or Π-shaped.

20. The LED according to claim 16, wherein The ligand includes a conjugated aromatic system.